A Low Cross-Polarization Microstrip Antenna Array for Millimeter Wave Applications - Yanzhi Fu; Yixiang Lin; Changda Shi (International Journal of Antennas and Propagation)
A low cross-polarization microstrip antenna array for millimeter wave (mmW) applications is proposed in this paper. The antenna element is composed of symmetric T-shaped patches with vias. The adoption of a double-sided symmetric radiation patch structure can suppress the cross-polarized electric field, and the vias reduces energy leakage during the power transmission along the antenna patches. To verify the concept, a 1 × 8 antenna array is fabricated and measured. The measured −10 dB impedance of the antenna array is 28.4% (31 GHz–41.5 GHz) and the peak gain is 15 dBi. The cross polarization ratio is above 35 dB and the 3 dB beamwidths on E-plane and H-plane are 7.5° and 135°, respectively. The proposed compact size and low cross-polarization antenna array might be a good choice for phased array radar and 5th generation (5G) mobile communication applications.